(untitled) (Eurasian Scientific Herald, 2023)
Diethyl 2,2’-((1,3,4-thiadiazol-2,5-diyl) bis (sulfandiyl) for nickel and cobalt ions in industrial and environmental facilities of "Almaliq KMK" JSC ) diacetate was selected as an organic analytical reagent. Immobilization of 2,2’-((1,3,4-thiadiazol-2,5-diyl) bis (sulfandiyl)) diacetate organic reagent on various fibrous carriers, determination of nickel and cobalt metal ions, and also an express method of determination are shown. Analytical and metrological parameters of the method were evaluated, it was found that the limit of determination of nickel and cobalt ions increases 20 times in the immobilized state compared to the solution.